Salinity-induced physiological, antioxidative, and enzymatic responses of ‘Oliana’ and ‘Lecciana’ olive tree cultivars - Hussain, Khalid; Fox, John-Paul; Hallman, Lukas M.; Shahid, Muhammad Adnan; Rossi, Lorenzo (Frontiers in Plant Science, 2026)
As land salinization intensifies across the United States, there is growing interest in cultivating salt-tolerant crops such as olives (Olea europaea). With extra virgin olive oil becoming an increasingly popular and valuable commodity in the U.S. market, growing olive cultivars that can thrive under challenging conditions is critical. This study evaluated the physiological, antioxidative and biochemical responses of two relatively newly introduced olive cultivars, ‘Oliana’ and ‘Lecciana’, to salinity stress under controlled greenhouse conditions. Eight-month-old plants were subjected to three salinity treatments (0, 50, and 100 mM NaCl) in a completely randomized design (n = 9). Plant gas exchange parameters were measured at 0, 15, 30, and 45 days after treatment, while chlorophyll content, fluorescence (Fv/Fm), biomass, nutrient accumulation (in leaves, stems, and roots), antioxidant enzyme activity, osmolyte levels, and reactive oxygen species (ROS) concentrations were assessed at 15, 30, and 45 days. Salinity stress significantly reduced gas exchange parameters in ‘Lecciana’ cultivar as compared to ‘Oliana’, resulting in decreased chlorophylls, Fv/Fm, and nutrient content. In response, antioxidant enzymes and osmolyte accumulation (proline and glycine betaine) increased with ‘Lecciana’ showing the strongest response. Conversely, lipid peroxidation and hydrogen peroxide (H2O2) levels were highest in ‘Oliana’ under 100 mM NaCl, indicating greater oxidative stress. These findings suggest that ‘Lecciana’s high salinity tolerance is associated with enhanced antioxidant defense and compatible solutes. In addition, ‘Lecciana’ and ‘Oliana’ could be a promising cultivar for saline and drought-prone regions of the U.S., supporting the expanding production of high-quality extra virgin olive oil.